Report of the Hospital Sub-committee - Horder, Thomas, 1871-1955 (London : Institutional Management Association)
1943-09-11 1943 1940s 15 pages MEMBERSHIP OF THE HOSPITAL SUB-COMMITTEE: *Mrs. D. Napier ... Chairman; Vice-Chairman of the Association, formerly Bursar of Lady Margaret Hall, Oxford. Miss M. Abrahams M.A., M.Sc. ... Formerly Dietitian to St. Bartholomew Hospital, London. Mrs. Cochrane, B.Sc. ... Factory Canteen Adviser, Ministry of Labour, formerly Food Supervisor to St. Bartholomew's Hospital, London. Miss A. Gregg ... Caterer at St. Thomas' Hospital, London. *Miss V. Norvick ... Secretary to the National Training and Diploma Committee of the Electrical Association for Women. Miss J. Robertson ... Catering Supervisor and Dietitian at the Watford and District Peace Memorial Hospital, Watford. Miss D. Skinner ... Canteen Section — Ministry of Supply, formerly trained Housekeeper — London County Council Hospitals. *Miss A. W. Watters ... Superintendent Housekeeper of the Royal Northern Hospital, London. *Miss E. Willans, M.B.E. ... Secretary of the Association of Teachers of Domestic Subjects and member of the Executive Committee of the Women's Gas Council. Miss A. Lumby ... Secretary of the Institutional Management Association. *Members of the Executive Committee of the Institutional Management Association 292/842/2/104